Functional diversification of the MADS-box gene family in fine-tuning the dimorphic transition of Talaromyces marneffei - Xueyan Hu; Yun Zhang; Juan Wang; Minghao Du; Yang Yang; James J. Cai; Ence Yang (mSystems, 2025)
ABSTRACT The dynamic transition between yeast and hypha is a crucial adaptive mechanism for many human pathogenic fungi, including Talaromyces marneffei, a thermodimorphic fungus responsible for causing fatal talaromycosis. In the current study, we elucidated the roles of the MADS-box family in fine-tuning the dimorphic transition in T. marneffei through functional diversification of members. Utilizing adaptive laboratory evolution, we identified an enrichment of MADS-box genes in mutants deficient in yeast-to-mycelium transition. Further phylogenetic analyses revealed a significant expansion of the MADS-box gene family within T. marneffei. Functional genetic manipulations revealed that overexpression of mads9, as opposed to its paralog mads10, effectively delayed the hypha-to-yeast transition. Through integrating RNA sequencing and chromatin immunoprecipitation sequencing, we demonstrated that mads9 and the previously characterized madsA (mads7) modulated the rate of hypha-to-yeast conversion by orchestrating metabolic pathways and membrane dynamics, respectively, with mutual regulation via shared target genes. Our findings illuminated the distinct functional roles of the MADS-box family in regulating dimorphic transitions in T. marneffei, offering new insights into fungal adaptability.IMPORTANCEThe dimorphic transition between yeast and hyphal forms in Talaromyces marneffei is a critical adaptive mechanism that underpins its pathogenicity, particularly in response to environmental cues such as temperature. In this study, we elucidated the role of the MADS-box transcription factor family and discovered that its members collaboratively regulate dimorphic transitions by assuming distinct roles in the morphogenesis, enhancing the understanding of the thermal adaptation of T. marneffei and the functional roles of the MADS-box gene family outside the plant.